An Analysis of Employee Work Posture Assessment with The Quick Exposure Check (QEC) Approach in The Green Tea Production in A Green Tea Company - Apriani, Dita; Hermana, Budi; Medikano, Alsen (SURYA TEKNIKA, 2024)
Candi Loka is a company engaged in the food sector, especially in producing green tea. Technology in the food sector is currently growing rapidly, resulting in a competitive competition. Candi Loka requires superior human resources to produce a high quality product. To realize this, it is necessary to carry out work with high accuracy and concentration by competent workers in their fields. The working conditions carried out by competent workers need to be considered because they greatly affect the work productivity. Uncomfortable working conditions will affect workers to have Musculoskeletal Disorders. The purpose of this study was to identify the musculoskeletal disorders developed by green tea production employees at Candi Loka and to identify the work posture of green tea production employees. Through this research, an assessment to find out the musculoskeletal disorders and to assess the work posture of workers in the green tea production section was carried out by using the QEC method. Pain complaints related to the musculoskeletal disorders that many workers in the green tea production department had were pain in the neck, shoulders, arms and back with a score of 40 and a proportion of 6.51%. The assessment of work posture by using the Quick Exposure Check (QEC) method for green tea processing workers had 79.09% E value with an action level of 4 and was included in the category of very dangerous risks and further action was needed as soon as possible, while tea sorting workers Green had an E value of 84.09% with an action level of 4 and was included in the very dangerous risk category and needed further action as soon as possible.